(untitled) (Marketing Journal, 2025)
This study explores the content, key principles, and functional tasks of strategic management of innovation activity in entrepreneurial entities from a scientific - theoretical and analytical perspective. The research substantiates the interrelation between the stages of strategic planning, implementation, and strategic control of innovation activities. Based on nationwide analysis, it has been determined that strategic management of innovation activity plays a crucial role in enhancing the competitiveness of entrepreneurial entities, ensuring efficient use of resources, and promoting sustainable economic development. The study employs qualitative research methods, including systematic and comparative analysis, content analysis, and scientific generalization. The results serve as a basis for developing scientific and practical recommendations aimed at improving innovation management mechanisms within entrepreneurial entities.